2023
DOI: 10.1039/d2cy01800d
|View full text |Cite
|
Sign up to set email alerts
|

Efficient lignin conversion over Ni/(Fe/Zn/Co/Mo/Cu)–WO3/Al2O3for selectively yielding alkyl phenols

Abstract: Alkyl phenols are mainly produced from non-renewable fossil-derived resources, of which the demand has been increasingly growing due to the rapid development of chemical industries. Due to the inherent aromaticity,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Comparison of monometallic and bimetallic catalysts (Tables , entries 1 and 4–7) revealed that doping of Ni and Fe metals led to a decrease in the selectivity of single product A (from 47.68 to 34.92% and 18.44%) but generated highly selective G7 and G3 products (Figure S1). This is due to the fact that different metal sites act differently and promote the generation of different products . 1%Co-1%Pd@NDCS showed the highest selectivity for the single product with a yield of 22.13 wt % and a selectivity of up to 60.83% (Table , entry 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of monometallic and bimetallic catalysts (Tables , entries 1 and 4–7) revealed that doping of Ni and Fe metals led to a decrease in the selectivity of single product A (from 47.68 to 34.92% and 18.44%) but generated highly selective G7 and G3 products (Figure S1). This is due to the fact that different metal sites act differently and promote the generation of different products . 1%Co-1%Pd@NDCS showed the highest selectivity for the single product with a yield of 22.13 wt % and a selectivity of up to 60.83% (Table , entry 4).…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the fact that different metal sites act differently and promote the generation of different products. 40 1%Co-1%Pd@NDCS showed the highest selectivity for the single product with a yield of 22.13 wt % and a selectivity of up to 60.83% (Table 1, entry 4). In summary, the bimetallic catalysts outperformed the monometallic catalysts, and Co−Pd@NDCS had the best catalytic performance and selectivity, which was subsequently used as a catalyst for the optimization of process conditions.…”
Section: Catalytic Hydrogenolysis Of Ligninmentioning
confidence: 99%
“…Lignin, as one of the abundant natural renewable resources, has been extensively researched in the field of fabricating aromatic products, biodegradable materials, and liquid fuels due to the specificity of its composition and structure. It has been found that lignin consists of coumarin (H), mustard alcohol (S), and pineal (G) groups, which are randomly connected by C–C/C–O bonds (4-O-5, α-O-4, β-O-4, β–β, β-1, etc.) to form natural aromatic polymer compounds with complex three-dimensional networks. In recent years, on the strength of the structural characteristics of lignin, it has been extensively demonstrated that lignin catalytic depolymerization (LCD) for liquid fuels and cooperative production of phenolic monomers is one of the promising methods for highly efficient utilization of lignin. , …”
Section: Introductionmentioning
confidence: 99%